Features of formation of gas cluster ion beams. (September 2015) - Korobeishchikov, N.G.; Kalyada, V.V.; Skovorodko, P.A.; Shmakov, A.A.; Khodakov, M.D.; Shulzhenko, G.I.; Voskoboynikov, R.V.; Zarvin, A.E.
Abstract: Results of experimental study of the formation of intensive gas cluster ion beams are presented. New applicable experimental equipment is described. The peculiarities of the formation and diagnostics of intensive cluster ion beams are discussed. Optimum conditions for forming the flow of neutral argon clusters beam with an intensity of up to 10 15  cluster/(cm 2 ·s) have been determined. It has been demonstrated that the increase in cluster beam intensity is limited by conservatism of the condensation process in supersonic gas jet. The available equipment allows one the formation of cluster ion beams with mean size of 10 3  atoms/cluster, energy of up to 25 keV and intensity of up to 5·10 13  ions/(cm 2 ·s). Mass composition of an accelerated cluster beam has been analysed by time-of-flight mass spectrometry. The numerical model for the parameters of the cluster beam is developed and found to predict the results which are in satisfactory agreement with the measured data. Highlights: Peculiarities of the formation of intensive cluster ion beams are discussed. New applicable experimental equipment is described. Intensity of cluster beams is limited by conservatism of the condensation process. Experimental results good agree with numerical solutions. Mass composition of cluster ion beam can be adjusted at the stage of it formation.